Aggressive Multimodal Approach for Anaplastic Thyroid Cancer and Long-Term Survival - Nasir Hussain; Usman Mustafa; Su Hyeon Jung; Alan D. Gilman (Case Reports in Oncological Medicine)
Anaplastic thyroid cancer (ATC) comprises 1-2% of all thyroid cancers and is one of the most aggressive cancers with a median survival rate of around four months. The average 5-year survival rate has been reported to be around 3.6%. In this paper, we have discussed management and prognostic variables of a patient with ATC who has survived for more than 5 years. A 59-year-old female was referred to our facility for an elective thyroid and parathyroidectomy for concerns of thyroid papillary cancer and hyperparathyroidism. At the time of surgery, the tumor mass had invaded the muscular layer of esophagus; radicle thyroidectomy parathyroidectomy along with removal of muscle layer of esophagus was performed, and diagnosis of ATC was made. The patient was treated with chemoradiation with a good treatment response and no recurrence of tumor for two and a half years until PET/CT followed by wedge biopsy of lung confirmed ATC recurrence. The patient was treated with another course of radiation treatment with a good treatment response. Since then, the patient has been following in our outpatient oncology clinic and has no evidence of tumor recurrence. Aggressive multimodal approach of combining radicle surgery with chemoradiation treatment in select patients of ATC with no distant metastasis helps improve prognosis.